Local Delivery of Senolytic Drug Inhibits Intervertebral Disc Degeneration and Restores Intervertebral Disc Structure. Issue 2 (5th November 2021) - Lim, Songhyun; An, Seong Bae; Jung, Mungyo; Joshi, Hari Prasad; Kumar, Hemant; Kim, Cheesue; Song, Seuk Young; Lee, Ju‐Ro; Kang, Mikyung; Han, Inbo; Kim, Byung‐Soo
Abstract: Intervertebral disc (IVD) degeneration (IVDD) is a leading cause of chronic low back pain. There is a strong clinical demand for more effective treatments for IVDD as conventional treatments provide only symptomatic relief rather than arresting IVDD progression. This study shows that senolytic therapy with local drug delivery can inhibit IVDD and restore IVD integrity. ABT263, a senolytic drug, is loaded in poly(lactic‐ co ‐glycolic acid) nanoparticles (PLGA‐ABT) and intradiscally administered into injury‐induced IVDD rat models. The single intradiscal injection of PLGA‐ABT may enable local delivery of the drug to avascular IVD, prevention of potential systemic toxicity caused by systemic administration of senolytic drug, and morbidity caused by repetitive injections of free drug into the IVD. The strategy results in the selective elimination of senescent cells from the degenerative IVD, reduces expressions of pro‐inflammatory cytokines and matrix proteases in the IVD, inhibits progression of IVDD, and even restores the IVD structure. This study demonstrates for the first time that local delivery of senolytic drug can effectively treat senescence‐associated IVDD. This approach can be extended to treat other types of senescence‐associated degenerative diseases. Abstract : This study applies senolytic therapy with local drug delivery to inhibit intervertebral disc (IVD) degeneration (IVDD) and restore integrity of IVD. ABT263 loaded in poly(lactic‐ co ‐glycolic acid) nanoparticles injected intradiscally reduces expressions of pro‐inflammatory cytokines and matrix proteases in the IVD, inhibits progression of IVDD, and restores the IVD structure in an injury‐induced IVDD rat model.